The Concept of Fair Pricing in the Regulation Framework of the Russian Securities Market - Semenkova, E.V.; Andrianova, L.N.; Krinichansky, K.V. (Journal of Reviews on Global Economics, 2018)
High risks and volatility in the stock market of Russia hinder the transformation of savings into investments and increase the speculative nature of transactions. Russian business does not use the securities market mechanism of financing investments widely enough. One of the causes of this is the faults in the model of securities market regulation in Russia and the legislative gaps. The aim of this article is developing suggestions concerning the improvement of government regulatory practice and self-regulation in securities market in Russia. The study is based on the methods of institutional, comparative and graphic analysis. Solving the problems connected with the set aim, the authors were the first to suggest the analysis of the relationship between the ability of the Russian capital markets to implement its allocative functions on the basis of fair pricing and the efficiency of the capital markets regulatory system. A relationship has been revealed between the speculative character of the Russian securities market and the faults in the model of its regulation. Suggestions have been grounded on the improvement of the existing rules and regulation in the Russian securities market, working out the foundations of long-term public policy for securities market regulation.